Narrative review: a study of pork DNA analysis methods in food gelatin - Ansor, Nisa Aulia; Hariyanti, Hariyanti; Rahmi, Hanifah (Universitas Ahmad Dahlan, 2023)
Gelatin is a substance resulting from the partial hydrolysis of collagen consisting of animal cartilage, skin, and bones from water-soluble polypeptides. The problem formulation in this study is what DNA analysis methods can be used to detect pig DNA in food gelatin. This study aimed to collect, review, and conclude information regarding the most widely used DNA analysis method to detect pig DNA in food gelatin. From the results of the literature study, it can be concluded that the most widely used extraction method in the analysis of porcine DNA in food gelatin is the DNeasy® Mericon Food kit extraction method for good purity results, there is the foodproof® III Kit method, the universal Wizard KIT Promega®, the DNeasy® Mericon Food kit, and the Column based FavorPrep™ Food DNA Extraction Kit. The pig DNA analysis method is widely used in conventional PCR. Sensitivity, fast testing time, and gh acporcine gelatin sample was identified by the appearance of a band on the electrophoresis results. Keywords: Food Gelatin, Extraction Method, DNA Analysis, Journal Review.